2021
DOI: 10.21037/atm-21-3913
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum albumin: a promising indicator of early mortality after surgery for infective endocarditis

Abstract: Background: Despite novel improvements in the diagnosis and treatment of infective endocarditis (IE), there has been no significant improvement in the survival rate of IE, which indicates that many details still need to be optimized in the preoperative assessment. We sought to evaluate preoperative serum albumin as a biomarker for predicting early mortality after IE surgery.Methods: Between October 2013 and June 2019, patients with a definite diagnosis of IE were enrolled in this study. Patients' albumin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Hypoalbuminemia reflects systemic inflammation, impaired antioxidant function, poor nutrient reserves, and potential kidney damage. 20 Thrombocytopenia reflects the severity of underlying sepsis and an elevated risks of hemorrhage. 44 Both are indicators of disease severity and the nature of the host response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoalbuminemia reflects systemic inflammation, impaired antioxidant function, poor nutrient reserves, and potential kidney damage. 20 Thrombocytopenia reflects the severity of underlying sepsis and an elevated risks of hemorrhage. 44 Both are indicators of disease severity and the nature of the host response.…”
Section: Discussionmentioning
confidence: 99%
“…Data of hospitalized patients who met the definite modified Duke criteria for IE, including native valve endocarditis and prosthetic valve endocarditis, were included in the present study as previously described. 20 Exclusion criteria were (1) did not have heart surgery, (2) pregnancy, (3) malignancy or life‐threatening diseases, and (4) missing data of interest. Data extracted from electronic medical records were (1) patient demographic characteristics, (2) medical history; (3) clinical symptoms and signs, (4) laboratory and echocardiographic findings, (5) surgery‐related information; and (6) discharge status and short‐term (30 days after surgery) follow‐up results.…”
Section: Methodsmentioning
confidence: 99%
“…However, prealbumin has not been used extensively in previous literature as a marker, possibly due to there being no established definition of malnutrition using prealbumin and a lack of inclusion in databases such as ACS‐NSQIP 24 . Therefore, although no specific marker is currently established as the single best measure of malnutrition, albumin level was used in this study since it was the most available nutritional marker in ACS‐NSQIP in addition to being one of the most frequently used markers for malnutrition in the scientific community due to its simplicity and ease 11–15,24,27,28 . We utilized the ACS‐NSQIP and concluded that within our cohort of transcervical ZD cases, hypoalbuminemia had no significant impact on postoperative outcomes following adjustment for demographics and related comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods that surgeons can use to screen for malnutrition in surgical patients, yet it is often underdiagnosed 10 . Serum albumin levels are commonly used as a marker to screen for malnutrition, with hypoalbuminemia typically classified as <3.5 g/dl 11–15 . Existing literature has found that hypoalbuminemia is associated with postoperative short‐term complications across procedures from multiple surgical subspecialties.…”
Section: Introductionmentioning
confidence: 99%
“…Serum albumin is closely linked to the patient's metabolic status. Hypoalbuminemia can indicate a hepatic insult, an immune disorder or a sepsisinduced catabolism [24]. Low serum albumin levels can also affect pharmacokinetics and pharmacodynamics by decreasing the extent of antibiotic bound to albumin, which increases the unbound fraction of the drug.…”
Section: Laboratory Testingmentioning
confidence: 99%